Insomnia and risk of cardiovascular disease: a meta-analysis - Sofi, Francesco; Cesari, Francesca; Casini, Alessandro; Macchi, Claudio; Abbate, Rosanna; Gensini, Gian Franco (European journal of preventive cardiology, 2014)
Increasing evidence suggests an association between insomnia and cardiovascular disease. We performed a systematic review with meta-analysis of all the available prospective studies that investigated the association between insomnia and risk of developing and/or dying from cardiovascular disease. Systematic review and meta-analysis of prospective cohort studies. We conducted an electronic literature search through MedLine, Embase, Google Scholar, Web of Science, The Cochrane Library and bibliographies of retrieved articles up to December 2011. Studies were included if they were prospective, had assessment of insomnia or sleep complaints at baseline, evaluated subjects free of cardiovascular disease at baseline and measured the association between insomnia and risk of developing and/or dying from cardiovascular disease. After the review process 13 prospective studies were included in the final analysis. These studies included 122,501 subjects followed for a time ranging from three to 20 years. A total of 6332 cardiovascular events occurred during the follow-up. Insomnia was assessed through questionnaire and defined as either difficulty of initiating or maintaining sleep or presence of restless, disturbed nights. The cumulative analysis for all the studies under a random-effects model showed that insomnia determined an increased risk (+45%) of developing or dying from cardiovascular disease during the follow-up (relative risk 1.45, 95% confidence interval 1.29-1.62; p < 0.00001), with no evidence of heterogeneity across the studies (I 2: 19%; p = 0.14). Insomnia is associated with an increased risk of developing and/or dying from cardiovascular disease.